A diet plan for Malay households using linear programming / Hasfaliza Tumin - Tumin, Hasfaliza (2011)
In recent years, the global economy influences the price of commodities, foods and services throughout the world. Unstable price of fuel and increase in prices of food stretch the household expenditures. Limited amount of money to spend for food leaves individual or household with restricted choice of food to purchase, thus, limiting their potential of adopting healthy diet. A prime concern is how can the Malaysian households, especially who live in urban areas and have low or moderate income, consume healthy diet with only a small amount of money reserved for food? This necessitates the need to develop a systematic way of planning the types and quantity of food to consume daily, which contains the required nutrition and can be acquired at minimal cost. This study proposed a daily diet plan which guides the families in selecting food which meets the dietary standard listed in the Malaysian Recommended Nutrients Intake (RNI) and at minimum cost. The objectives of this study are to create a database of commonly consumed food in Malaysia with their respective nutritional contents and estimated costs, to develop a mathematical model that minimizes daily cost for food that meets the Malaysian RNI and to produce an interface which allows users to generate their healthy diet plan. Linear programming (LP) model is employed in solving this problem and producing the combinations of healthy daily meals inclusive of breakfast, lunch and dinner furnished with the estimated daily diet cost. The diet plan generated can be recommended to the public and the associated minimum cost can be used as a guideline for estimating monthly budget for food. The diet plan developed in this study can also be easily modified to be used for specific range of budgets allocated monthly for food, thus, it may also be of interest to all income groups.